Obstructive sleep apnoea in craniofacial microsomia: a systematic review. Issue 5 (May 2015) - Caron, C.J.J.M.; Pluijmers, B.I.; Joosten, K.F.M.; Mathijssen, I.M.J.; van der Schroeff, M.P.; Dunaway, D.J.; Wolvius, E.B.; Koudstaal, M.J.
Abstract Children with craniofacial microsomia (CFM) are at risk of obstructive sleep apnoea (OSA). This systematic review provides an overview of the literature on the prevalence of OSA in children with CFM. A search was performed in PubMed, Embase, Cochrane Library, and Web of Science for articles on CFM and OSA. The following data were extracted from the articles: number of patients, patient characteristics, presence of OSA, polysomnography outcomes, and the treatments and outcomes of OSA. We included 16 articles on CFM and OSA, four of which reported the prevalence of OSA (range 7–67%). Surgical treatment was more often described in these patients than conservative treatment. According to the literature, OSA is related to CFM. However, as there have been no prospective studies and few studies have presented objective measurements, no definitive conclusions can be drawn. Prospective studies are needed to determine the prevalence of OSA in patients with CFM.